Identificación de la secuencia tipo st78 de xylella Fastidiosa en olivo de Argentina - Tolocka, Patricia; Guzman, Fabiana; Paccioretti, Mauro Andres; Roca, M.E.; Otero, Maria Laura; Haelterman, Raquel Mercedes (Asociación Argentina de Fitopatólogos, 2021)
Poster